Predictive role of vitamin A serum concentration in psoriatic patients treated with IL-17 inhibitors to prevent skin and systemic fungal infections - Campione Elena; Cosio Terenzio; Lanna Caterina; Mazzilli Sara; Ventura Alessandra; Dika Emi; Gaziano Roberta; Dattola Annunziata; Candi Eleonora; Bianchi Luca (Elsevier, 2020)
The use of biological drugs in psoriasis is replacing traditional therapies due to their specific mechanism and limited side effects. However, the use of Interleukin 17 inhibitors and the modification of its cytokine pathway could favor the risk of fungal infections.All-trans retinoic acid is an active metabolite of vitamin A with anti-inflammatory and immunoregulatory properties through its capacity to stimulate both innate and adaptive immunity and to its effects on proliferation, differentiation and apoptosis in a variety of immune cells. Furthermore, it has been recently discovered that All-trans retinoic acid has a direct fungistatic effect against Candida and Aspergillus Fumigatus.On the basis of these new insights, in the current review, we suggest that the evaluation of serum level of All-trans retinoic acid or vitamin A should be considered as a predictive marker for the development of fungal infections among psoriatic patients treated with Interleukin 17 inhibitors.In clinical practice, vitamin A test could be added in the routine hospital diagnostic management for a better selection of psoriatic patients eligible to Interleukin 17 inhibitors.